Homeostatic nuclear RAGE–ATM interaction is essential for efficient DNA repair. Issue 18 (9th August 2017) - Kumar, Varun; Fleming, Thomas; Terjung, Stefan; Gorzelanny, Christian; Gebhardt, Christoffer; Agrawal, Raman; Mall, Marcus A.; Ranzinger, Julia; Zeier, Martin; Madhusudhan, Thati; Ranjan, Satish; Isermann, Berend; et al.
Abstract: The integrity of genome is a prerequisite for healthy life. Indeed, defects in DNA repair have been associated with several human diseases, including tissue-fibrosis, neurodegeneration and cancer. Despite decades of extensive research, the spatio-mechanical processes of double-strand break (DSB)-repair, especially the auxiliary factor(s) that can stimulate accurate and timely repair, have remained elusive. Here, we report an ATM-kinase dependent, unforeseen function of the nuclear isoform of the R eceptor for A dvanced G lycation E nd-products (nRAGE) in DSB-repair. RAGE is phosphorylated at Serine 376 and Serine 389 by the ATM kinase and is recruited to the site of DNA-DSBs via an early DNA damage response. nRAGE preferentially co-localized with the MRE11 nuclease subunit of the MRN complex and orchestrates its nucleolytic activity to the ATR kinase signaling. This promotes efficient RPA2 S4-S8 and CHK1 S345 phosphorylation and thereby prevents cellular senescence, IPF and carcinoma formation. Accordingly, loss of RAGE causatively linked to perpetual DSBs signaling, cellular senescence and fibrosis. Importantly, in a mouse model of idiopathic pulmonary fibrosis (RAGE −/− ), reconstitution of RAGE efficiently restored DSB-repair and reversed pathological anomalies. Collectively, this study identifies nRAGE as a master regulator of DSB-repair, the absence of which orchestrates persistent DSB signaling to senescence, tissue-fibrosis and oncogenesis.